Detection of Salmonella sp. and Escherichia coli Contamination on Processed Fish Meat - Putri, Monica Karunia; Oktari, Agung; Oktiansyah, Rian; Ulandari, Tiara (MAXIMUS: Journal of Biological and Life Sciences, 2023)
Fish is a processed food ingredient with very high water content, causing fish to become perishable due to the growth of bacteria in fish. One of the foods made from processed fish is pempek. Therefore, carrying out excellent handling and processing of these processed food ingredients is necessary. This study aims to detect the presence of Salmonella sp bacteria with SSA (Salmonella Shigella Agar) media and E-coli with EMBA (Eosin Methylene Blue Agar) media in processed food derived from ground fish, namely pempek. Three samples were taken from several Palembang city snacks. The method used is a prediction test by streaking samples on selective media SSA and EMBA scratching. The results showed that all food samples tested to detect the presence of Salmonella sp. using SSA media showed positive results. The detection test results for the contamination of E-coli using EMBA media on the food samples also showed that three samples of pempek made from flour and processed ground fish meat positively contained E-coli bacteria.